Parking slabs made of carbon reinforced concrete. (21st November 2017) - Schumann, Alexander; Michler, Harald; Schladitz, Frank; Curbach, Manfred
Abstract : Parking garage buildings are usually comprised of steel reinforced concrete (RC) slabs. Unfortunately, there are often cases of damage caused by the high exposure to corrosive chemicals. To prevent corrosion of the reinforcement, especially the ceilings must be coated with expensive protection systems. Due to the not‐corrosive nature of carbon fibers, carbon RC is a perfect solution for those structures. But before using carbon RC for parking slabs, the problem of the end anchorage of the reinforcement by short‐end anchorage lengths had to be solved. Therefore, a new anchorage method for carbon RC is described in detail in this publication. A large‐scale test had been conducted to show the potential of carbon RC for parking slabs and to prove the ability of the developed new‐end anchorage method. Also, an analytical recalculation of the large‐scale test is presented.